Effect of window-to-wall-area ratio on thermal performance of building wall materials in Elazig, Turkey - Ozel, Meral; Ozel, Cihan (Public Library Science, 2020)
In this study, the effect of glazing-to-total-wall-area ratio on the thermal performance of different wall materials is numerically investigated in terms of heat transmission load. The investigation was performed for a South-facing wall in Elazig, Turkey. The heat transmission load through walls and windows are determined separately for summer and winter climate conditions. In this analysis, the frame area of the window is not considered. Therefore, whereas the glazing area on uninsulated and insulated walls is increased from 0% to 100%, the heat gain and losses are calculated separately according to the glazing type. The transmission loads through the wall are determined by an implicit finite difference procedure under steady periodic conditions. Concrete, briquettes, bricks, and autoclaved aerated concrete are selected as structure materials. Results show that in the uninsulated wall, the wall material affected the glazing area, whereas in the insulated wall, the effect of wall material on glazing area is insignificant.
Keywords: Optimum Insulation Thickness; Energy-Consumption; Orientation; Location; Roof